The effect of pasteurized milk and pure soy milk on enamel remineralization - Metly, Annesha; Sumantri, Dedi; Oenzil, Fadil (Padjadjaran Journal of Dentistry, 2019)
Introduction: Tooth remineralization agent can be found in pasteurized milk and soy milk. Ca2+ and PO43- ions concentration in both products inhibited hydroxyapatite dissolution and enhanced remineralization. This study was aimed to investigate the effect of pasteurized milk and pure soy milk on tooth enamel remineralization. Methods: This study was an experimental laboratory with pre-test post-test control group design. Twenty-seven maxillary premolars were divided into 3 groups; 37% phosphoric acid used to demineralized the samples followed by initial enamel hardness measurement. All samples were immersed in aquadest, pasteurized milk, and pure soy milk for 14 days, 102 minutes per day. Final enamel hardness was measured with the Vickers hardness test. Results: Increasing enamel hardness was found in all groups. Two-way ANOVA test was used to compare the increase of enamel hardness in all group, which showed the p-value = 0.002. Post-hoc LSD test was then used to compare the increase of the enamel hardness in pasteurized milk and pure soy milk groups, which resulted in the p-value = 0.147. Conclusion: There was an effect of pasteurized milk and pure soy milk group on enamel remineralization. However, there was no difference in the increase of enamel hardness value between pasteurized milk and pure soy milk groups.Keywords: Pasteurized milk, pure soy milk, tooth enamel, remineralization.